Two years follow-up of relapsing eosinophilic pneumonia with concomitant severe asthma successfully treated with benralizumab: A case report and brief review of the literature. (2023) - Angeletti, G.; Mazzolini, M.; Rocca, A.
Abstract: Relapsing eosinophilic pneumonia and severe eosinophilic asthma are rare and disabling diseases, which share common inflammatory backgrounds and often require long-term systemic steroid therapy. Benralizumab is a humanized antibody targeting IL-5 receptor that reduces corticosteroid dependence and flares up in severe eosinophilic asthma on long term. In this case report, successful treatment of eosinophilic pneumonia and severe eosinophilic asthma with benralizumab is described after a 2-year follow up, showing the promising results of this therapy for eosinophilic pneumonia management.